Weight Status and Associated Risk Factors of Mealtime Behaviours among Children with Autism Spectrum Disorder - Maizatul Naqiah Zulkifli; Masne Kadar; Nur Hana Hamzaid (MDPI AG, 2022)
Atypical mealtime behaviours in children with autism spectrum disorder (ASD) have been linked with oral sensory hypersensitivity that may contribute to food selectivity and weight issues. This cross-sectional study aims to determine the association between atypical mealtime behaviours and associated risk factors besides exploring the prevalence of overweight and obesity among Malaysian children with ASD in community settings. A total of 150 children with ASD aged 3-11 years participated in this study. A self-administered questionnaire on sociodemographic variables, mealtime behaviours and oral sensory processing was completed by the caregivers. The prevalence of overweight in the study samples was 18.5%, whereas obesity was 20.0%. In a multivariate analysis model, oral sensory processing (B = 0.608, 95% CI = 0.493, 0.722, p < 0.001), severity of autism symptoms (moderate and severe) (B = 2.585, 95% CI = 0.722, 4.448, p = 0.007) and younger children with ASD (B = −0.694, 95% CI = −1.189, −0.199, p = 0.006) were found as independent predictors of atypical mealtime behaviours. Children with ASD aged 3-11 years old have a higher prevalence of being overweight and obese, thus requiring regular anthropometric screening in community settings by relevant healthcare professionals. Furthermore, a relationship was found between oral sensory difficulties and atypical mealtime behaviours in children with ASD. A multidisciplinary approach is crucial in the overall management of food selectivity in this population.